Metformin promotes the survival of transplanted cardiosphere-derived cells thereby enhancing their therapeutic effect against myocardial infarction. Issue 1 (December 2017) - Yue, Rongchuan; Fu, Wenbin; Liao, Xiang; Lan, Cong; Liao, Qiao; Li, Liangpeng; Yang, Dezhong; Xia, Xuewei; Chen, Xiongwen; Zeng, Chunyu; Wang, Wei
Abstract Background Transplantation of cardiosphere-derived cells (CDCs) has been shown to exert a therapeutic effect in patients with myocardial infarction (MI). However, poor survival of transplanted CDCs limits their beneficial effect. Metformin (MET) activates AMP-activated protein kinase (AMPK) which is associated with cell survival. The aim of this study is to determine whether MET improves CDC survival in the transplantation microenvironment and enhances the therapeutic effect of CDC transplantation against MI. Methods CDCs were isolated and expanded from transgenic β-actin-GFP mice. CDCs were pretreated with MET and intramyocardially injected into wild-type C57 mouse heart with MI injury. The survival of CDCs was quantified, and the infarct size and cardiac function of treated hearts were evaluated. Results CDC transplantation modestly reduced infarct size and improved cardiac function in the post-MI heart, which was further improved by MET treatment. MET pretreatment significantly increased the survival of CDCs transplanted into the myocardium. MET also reduced CDC apoptosis induced by oxidative stress in vitro. The anti-apoptotic effect of MET was blocked by the AMPK inhibitor compound C. MET increased AMPK phosphorylation and upregulated endothelial nitric oxide synthase (eNOS) in CDCs under oxidative stress, which might be associated with the anti-apoptotic effect of MET. Conclusions MET improves the survival of transplanted CDCs in the myocardium, thereby enhancing their therapeutic effect against MI injury. The pro-survival function of MET on CDCs might be associated with an AMPK-eNOS-dependent mechanism.